2017
DOI: 10.1186/s12870-017-0983-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and diversification of the miR166 family in soybean and potential roles of newly identified miR166s

Abstract: BackgroundmicroRNA166 (miR166) is a highly conserved family of miRNAs implicated in a wide range of cellular and physiological processes in plants. miR166 family generally comprises multiple miR166 members in plants, which might exhibit functional redundancy and specificity. The soybean miR166 family consists of 21 members according to the miRBase database. However, the evolutionary conservation and functional diversification of miR166 family members in soybean remain poorly understood.ResultsWe identified fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 52 publications
4
46
0
Order By: Relevance
“…These observations support conservation of the miR166k-166h polycistron in the Oryza genus ( Baldrich et al, 2016 ). miR166 clusters have been identified in the genome of several plant species (e.g., M. truncatula , soybean and Physcomitrella patens ) but, in most cases, the polycistronic nature of these miR166 clusters has not been demonstrated ( Boualem et al, 2008 ; Zhang et al, 2009 ; Barik et al, 2014 ; Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations support conservation of the miR166k-166h polycistron in the Oryza genus ( Baldrich et al, 2016 ). miR166 clusters have been identified in the genome of several plant species (e.g., M. truncatula , soybean and Physcomitrella patens ) but, in most cases, the polycistronic nature of these miR166 clusters has not been demonstrated ( Boualem et al, 2008 ; Zhang et al, 2009 ; Barik et al, 2014 ; Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, miR166b has been reported to target rice RDD1 ( rice Dof daily fluctuations 1 ), a non- HD-ZIP III transcription factor involved in nutrient uptake and accumulation ( Iwamoto and Tagiri, 2016 ). Very recently, miR166-guided cleavage of ATHB14-LIKE transcripts encoding a homeobox-leucine zipper protein has been described in soybean ( Li et al, 2017 ). In M. truncatula , a miR166 polycistron containing two copies of miR166a targeting HD-ZIP III transcripts was found to control root architecture and nodule development after infection by Sinorhizobium meliloti ( Boualem et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these miRNAs, some have been shown to play roles in plant stress resistance and seed development. The miR166 target ATHB14-LIKE transcript was experimentally validated by RACE PCR 36 . The expression patterns of the miR166s and 12 target genes were examined during seed development and in response to abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a miR160resistant version of ARF17 in plants causes dramatic developmental defects, and overexpression of miR160 results in fewer starch granules and disorganized root tips [52,53]. Analysis of the conservation and diversification of the miR166 family in plants showed that miR166 members play a wide and important regulatory role in seed development [54]. Therefore, these data suggest that these miRNAs have multiple regulatory functions in grain filling.…”
Section: Mirnas Involved In Wheat Grain Developmentmentioning
confidence: 91%